B7-H3 specific T cells with chimeric antigen receptor and decoy PD-1 receptors eradicate established solid human tumors in mouse models. (1st January 2020) - Huang, Baozhu; Luo, Liqun; Wang, Jun; He, Bailin; Feng, Rui; Xian, Na; Zhang, Qiong; Chen, Lieping; Huang, Gangxiong
ABSTRACT: The application of chimeric antigen receptor (CAR)-T cell therapy in patients with advanced solid tumors remains a significant challenge. Simultaneously targeting antigen and the solid tumor microenvironment are two major factors that greatly impact CAR-T cell therapy outcomes. In this study, we engineered CAR-T cells to specifically target B7-H3, a protein commonly found in solid human tumors, using a single-chain variable fragment (scFv) derived from an anti-B7-H3 monoclonal antibody. We tested the antitumor activity of B7-H3 CAR-T cells in mouse models with solid human tumors and determined that B7-H3 CAR-T cells exhibited potent antitumor activity against B7-H3 + tumor cells in vitro and in vivo . In addition, PD-1 decoy receptors were engineered to include extracellular PD-1 fused to the intracellular stimulatory domain of either CD28 or IL-7 receptor, respectively, which were then introduced into B7-H3 CAR-T cells. As a result, these newly modified, superior CAR-T cells exhibited more persistent antitumor activity in B7-H3 + /B7-H1 + tumors in vivo . Our findings indicate that B7-H3 specific CAR-T cells have the potential to treat multiple types of advanced solid tumors.